The role and regulation of erythropoietin (EPO) and its receptor in skeletal muscle: how much do we really know? - Lamon, Séverine; Russell, Aaron P. (Frontiers in Physiology, 2013)
Erythropoietin (EPO) primarily activates erythroid cell proliferation and growth and is active in several types of non-hematopoietic cells via its interaction with the EPO-receptor (EPO-R). This review focuses on the role of EPO in skeletal muscle. The EPO-R is expressed in skeletal muscle cells and EPO may promote myoblast differentiation and survival via the activation of the same signaling cascades as in hematopoietic cells, such as STAT5, MAPK and Akt. Inconsistent results exist with respect to the detection of the EPO-R mRNA and protein in muscle cells, tissue and across species and the use of non-specific EPO-R antibodies contributes to this problem. Additionally, the inability to reproducibly detect an activation of the known EPO-induced signaling pathways in skeletal muscle questions the functionality of the EPO-R in muscle in vivo. These equivocal findings make it difficult to distinguish between a direct effect of EPO on skeletal muscle, via the activation of its receptor, and an indirect effect resulting from a better oxygen supply to the muscle. Consequently, the precise role of EPO in skeletal muscle and its regulatory mechanism/s remain to be elucidated. Further studies are required to comprehensively establish the importance of EPO and its function in skeletal muscle health.